Toksisitas Isolat Lokal Bacillus thuringiensis (H-14) serta Lama Efektivitasnya di dalam Air terhadap Larva Nyamuk Anopheles farauti Laveran - Daniel Lantang (Jurusan Biologi FMIPA Universitas Cenderawasih, 2010)
The research of toxicity local isolate Bacillus thurigiensis (H-14) and 18 codeword isolate along the efectivity on the water concerning to the Anopheles. The research aim to acquainted about the toxicity of B. thuringiensis isolate H-14 local and 18 codeword isolate along of the toxicity on the water concerning to the Anopheles. The methode is laboratory experiment wich used complete randome, analysis the data to wich BNJ test and α..05. The result shows that isolate of local B. huringiensis H-14 Anopheles farauti Laveran B.thurngiensis H-14 0.06 ml concentrate, 0.08 ml concentrate and 0.1 of effective of the A.farauti death until 6 day, and concentrate 0.1 ml effective show the Anopheles death until 7 day. Analysis varians shows the different act control concentrate in the other side, the act of concentrate isnt different significant. Key words: Toxic, Bacillus thuringiensis, Anopheles farauti Laveran.